Musical-aesthetic education in an adolescent psychiatric ward: a case study (Orfeu, 2021)
This paper presents a musical-aesthetic educational project which combined the piano piece Faschingsschwank aus Wien by Robert Schumann and improvisations of adolescent patients in a psychiatric ward. The patients explored both musical and non-musical material, such as pictures and masks. They could bring in their own ideas, not only in designing the masks and in the improvisation, but also in the development of the choreography. At the end of the project, the results were presented in a final performance. As part of the project, interviews with participants and hospital staff were conducted and qualitatively analysed. The participants clearly expressed a changed perception of themselves. These transformations can be interpreted as indicators of musical-aesthetic educational processes. This case study constitutes a contribution to music education research in hospitals and may even encourage the implementation of similar educational offers in hospitals in the future.